The Penguin dictionary of building - Maclean, James H. (Penguin reference books, 1995)
Do you need to know your lime putty from your lime plaster? Want to improve your flatness tolerance? Stuck with an incomprehensible DIY manual? This dictionary provides explanations of the techniques, equipment and issues of the building world. It is intended for students, carpenters, glaziers, plasterers, and others.